2018
DOI: 10.1017/ice.2018.60
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Healthcare-Associated Infections in Mainland China: A Systematic Review and Meta-analysis

Abstract: OBJECTIVETo assess the prevalence of healthcare-associated infections (HAIs) in mainland China.DESIGNSystematic review and meta-analysis.SETTINGAdults and children from secondary and tertiary acute-care hospitals in mainland China.METHODSWe searched PubMed, the China National Knowledge Infrastructure, and Wan Fang for multicenter point-prevalence surveys of acute-care hospitals in mainland China from January 2006 to August 2016. All reports related to HAI, using a point-prevalence methodology and published eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 27 publications
(62 reference statements)
3
51
3
2
Order By: Relevance
“…From the study, the national pooled prevalence of HCAI in Ethiopia was 16.96% (95% CI: 14.10%-19.82%). The result was higher than studies conducted in China (3.12%) [ 35 ], Morocco (10.3%) [ 36 ], Botswana (13.54%) [ 6 ], and South Africa (7.67%) [ 7 ]. The possible reasons for high prevalence in this study might be very low hand hygiene practice by physicians and resource constraints [ 37 ], low adherence to infection prevention practice [ 38 ], low level of job satisfaction [ 39 ], morally distressed nurses [ 40 ], and low implementation of the nursing process [ 41 ] in our settings, and also less attention given to HCAI.…”
Section: Discussionmentioning
confidence: 59%
“…From the study, the national pooled prevalence of HCAI in Ethiopia was 16.96% (95% CI: 14.10%-19.82%). The result was higher than studies conducted in China (3.12%) [ 35 ], Morocco (10.3%) [ 36 ], Botswana (13.54%) [ 6 ], and South Africa (7.67%) [ 7 ]. The possible reasons for high prevalence in this study might be very low hand hygiene practice by physicians and resource constraints [ 37 ], low adherence to infection prevention practice [ 38 ], low level of job satisfaction [ 39 ], morally distressed nurses [ 40 ], and low implementation of the nursing process [ 41 ] in our settings, and also less attention given to HCAI.…”
Section: Discussionmentioning
confidence: 59%
“…Health care-associated infection (HAI) is an infection occurring in a patient during the process of care in a hospital or other health-care facility, which was not present or incubating at the time of admission. HAIs can also appear after discharge from the hospital and include occupational infections among hospital/health-care staff [ 1 , 2 , 3 ]. HAIs result in considerable human suffering and financial losses on account of prolonged hospital stays, increased morbidity and mortality, additional diagnostic and therapeutic interventions and antimicrobial resistance [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter baumannii is one of the most common nosocomial pathogens in Asia and South America. 1 A systematic review has revealed that A. baumannii accounted for 11.28% of nosocomial infections in general hospitals in China, making it the third most common nosocomial pathogen, 2 and carbapenem-resistant A. baumannii (CRAB) has emerged worldwide. As early as 2013, the US Centers for Disease Control and Prevention listed multidrug-resistant A. baumannii (MDRAB) including CRAB as a serious threat, 3 and the WHO listed CRAB as one of the three most critical threats in a global drug-resistant warning in 2017.…”
Section: Introductionmentioning
confidence: 99%